Quelques caractéristiques du lexique acadien - Gérin, Pierre M. (Studia Romanica Posnaniensia, 2017)
This article constitutes a study of the composition of Acadian lexical units as well as the main methods of lexical unit formation: archaisms, regionalisms, lexical borrowing from Amerindian languages and English. We conclude our study with a look at an important characteristic of this vocabulary, the use on land of maritime terminology.